ANALISA PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) PADA LAPORAN KEUANGAN SKATERS SHOP DISTRO - Tasum Tasum SE., M.Si (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
This study examines Micro, Small and Medium Entity Financial Accounting Standards (MSME) Skaters Shop Distros. The population in this study is the recapitulation of recording cash disbursements, cash receipts, and merchandise inventory Skaters Shop Distro. The sampling technique in this study uses non probability sampling with purposive sampling technique. In this study, the data or information obtained by the author were analyzed qualitatively with a descriptive approach. The result of this study is that the understanding of Skaters Shop Distro owners about Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) is still very low. Recording and preparing financial statements is still very simple and in accordance with the needs and understanding of the owner. Skaters Shop Distro has not applied the Financial Accounting Standards for Micro, Small and Medium Enterprises (SAK EMKM) because they still do not understand about SAK EMKM and its limited time and human resources.